Building assets from birth: Singapore's policies. Issue 1 (2nd January 2019) - Loke, Vernon; Sherraden, Michael
ABSTRACT: Singapore has created innovative, inclusive and comprehensive asset-building policies designed to promote social stability and development. Asset building from early childhood is an important part of this overall strategy. In 1993, Singapore's government initiated a universal child asset-building policy, Edusave, which provides resources for improving educational outcomes. Since then, three additional asset-building policies for children have been implemented: the Baby Bonus and Child Development Accounts (CDAs), Post-Secondary Education Accounts (PSEAs) and Medisave, a health savings account. We discuss each of these asset-building accounts for children in Singapore. We point out distinctive features and assess key elements in overall policy design.